Manajemen Peningkatan Mutu Pembiayaan Sarana dan Prasarana Dalam Strategi Meningkatkan Layanan Pendidikan Di MTs Nurul Amien Lenteng Barat Lenteng Sumenep - Rafiuddin, Moh.; Maimun, Maimun; Khatimah, Khusnul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
The aim of this research is to explore the management strategies employed to enhance the quality of financing for facilities and infrastructure as part of efforts to improve the implementation of education at MTS Nurul Amin. This study adopts a qualitative approach, as the research is conducted directly in the field, with data being collected through various methods such as interviews, observations, and documentation. The primary findings of the research indicate that the policies related to the development of facilities and infrastructure are continuously evolving and showing significant progress, largely due to the effective performance of both the school principal and the teachers. Their collaborative efforts have played a key role in driving improvements, thereby establishing a solid strategy for enhancing the overall educational services at MTS Nurul Amin. These improvements not only reflect better resource management but also contribute to more effective teaching and learning processes, ensuring that the institution remains competitive and capable of delivering quality education.